The role of training courses in history and their relationship to the acquisition of some educational media skills from the point of view of history teachers in the middle school - Rasha Neama Aylan (Journal of College of Education, 2024)
It aims to develop teacher skills, develop and renew educational concepts, diversify teaching methods, and the emergence of innovations in the field of educational techniques. The study aimed to identify training courses and their relationship to the acquisition of some educational media skills. It followed the descriptive, correlational approach. The study population consisted of middle school teachers in the Kut and Al-Baghd districts. They numbered (804) male and female teachers, and the study sample consisted of one hundred and twenty-four (124) teachers. The data was collected, analyzed and processed through the statistical packages program (Spss). The study reached several results, the most important of which are: the role of training courses in equipping middle school teachers with Kut District, the skills of using educational media are high, the level of selection of the educational media by the middle school teachers in the Kut Center is very high, the level of the use of the educational media by the middle school teachers in Kut District is a statistically significant relationship between the training courses and the acquisition of skills in using educational media